2013
DOI: 10.1002/job.1851
|View full text |Cite
|
Sign up to set email alerts
|

When mentors feel supported: Relationships with mentoring functions and protégés' perceived organizational support

Abstract: Summary We surveyed full‐time employees of ongoing mentoring relationships to investigate relationships among mentors' perceived organizational support (POS), the extent of mentoring functions protégés received, and protégés' POS. Moreover, we examined the moderating role of mentors' altruistic personality in the relationship between mentors' POS and mentoring functions received. Results showed that mentors' POS was positively related to the extent of mentoring protégés reported receiving, which was then relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 48 publications
4
52
0
2
Order By: Relevance
“…Prior research [18,22,34,65] has suggested that managerial coaching and mentoring have a critical impact on developing employees' potential capabilities. As uncertainty makes predicting the future impossible and complexity increases, the sustainability of enterprises has become dependent on finding ways to realize and improve employees' potential capabilities.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research [18,22,34,65] has suggested that managerial coaching and mentoring have a critical impact on developing employees' potential capabilities. As uncertainty makes predicting the future impossible and complexity increases, the sustainability of enterprises has become dependent on finding ways to realize and improve employees' potential capabilities.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…A number of studies have proclaimed that mentoring fosters protégés' wisdom when compared to non-mentored employees in the same organizations [17,18,37,41]. These previous studies revealed that mentoring positively affects both job satisfaction and organizational commitment [19].…”
Section: Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the organizational support theory, when in an unfamiliar environment, engineering masters would usually be at loose ends, and have a feeling of pressure, but enterprise support can relieve employees' feeling of tension and pressure, while formal mentor system is just a kind of organizational support [6]. Consequently, when enterprise mentors provide assistance and support to engineering masters, they would perceive it and feel obliged to pay back the support, enhance their organizational commitment and adapt to their social identity in the role as a member, to repay mentors and enterprises with better practice performance [14]. Specifically, career guidance would help engineering masters to learn new knowledge and skills by setting challenging tasks for them, which would help establish related career competency directly, while psychological guidance would improve the self-efficacy and organizational identification through feedbacks and suggestions (Day & Allen, 2004), which is consistent with high performance.…”
Section: Mentors' Guidance and Practice Performance Of Engineering Mamentioning
confidence: 99%
“…Lee and Shen (2013) took customer' satisfaction as the key for quality improvement, and insisted on the factors in customers including (2) the quality of the service structure, such as the cleanness of facilities, convenience of traffic facilities, qualities of the servant and the care degree for customers' benefits; (3) the quality of service outcome -the overall awareness for service. Hu et al (2014) argued that the core of the CSI is based on comparable evaluation of the gap between the expectation to the products before the activity of purchase and the perception after consumption. The core essence of satisfaction degree is a kind of evaluation based on comparison.…”
Section: Customer Satisfaction Index (Csi)mentioning
confidence: 99%